SANITAIR MALANG INDUSTRY CENTER: OPTIMIZING OF IMPLEMENTATION CREATIVE ECONOMIC IN DEALING ECONOMIC INEQUALITY IN INDONESIA - Muhammad Akhyar; Nuroniatul Khusnia (UNEJ e-Proceeding)
The creative economy is an economic concept that emphasizes creativity and knowledge as the main asset in moving the economy. Creative economy which is the transformation structure of the world economy that is becoming the new high sector potential in encouraging economic growth in Indonesia. The change of economic growth from natural resources to human resources, from the agricultural era into the industrial age and the information. One of the potential of economic creative sector is a sector or crafts that influencer 15.70 % to GDP in Indonesia 2015. One of them is Industrial Centers Sanitair in Malang. The aims of this research to describe the quality of human resources in Industrial centers sanitair Karangbesuki also the strategies are applied to increase the quality of human resources in industrial centers Sanitair Karangbesuki. This type of resource is Qualitative resource with Descriptive qualitative approach. Result of this research show that to develop the quality of human resource in industrial centers sanitair has found strategies to increase the quality of human resources and creative to face the economic inequality in Indonesia.